Complex processes related to the early stages of mercury electrodeposition on Pt electrodes - Salvarezza, Roberto Carlos (1988)
The underpotential deposition and early stages of bulk mercury electrodeposition on platinum from aqueous solution containing Hg2+2 ions were studied by using combined potentiostatic and potentiodynamic techniques. The simultaneous electroreduction of the O-containing surface species and the underpotential deposition of Hgsup>2+2 ions render an electrode surface containing an O/Hg atom ratio which depends on both the applied potential and Hgsup>2+2 ion concentration in solution. The nucleation and growth of bulk mercury is impeded by the presence of O-containing surface species, whereas it is markedly enhanced by the presence of Hg-adatoms on the electrode surface. A small number of sites are involved in the nucleation process. Apparently defective points at the UPD Hg layer act as preferred sites for nucleation. It takes potentials more negative than the reversible potential of the Hg/Hgsup>2+2 ion electrode and relatively long electrodeposition times to achieve a degree of surface coverage by mercury atoms greater than 1. It is possible to observe that a fraction of them penetrates into bulk platinum to form a skin-type Hg-Pt alloy.